Medicinal Plant Images - Cook, Alaistair (Pharmacognosy Communications)
Backhousia citriodora (lemon myrtle) is an Australian plant, native to the subtropical areas of eastern Australia. B. Citriodora leaves have good, broad-spectrum antinmicrobial acitivity.[1,2] This photograph was taken in Brisbane, Australia by Dr Ian Cock in February 2010.